Understanding the impact of racism on surgical outcomes in settler nation-states USA and Canada: a protocol for a systematic review and meta-analysis - Mary Brindle; Oluwatomilayo Daodu; Tyara Marchand; Saffa Aziz; Ifeoluwa Adedipe; Mirna Matta (BMJ Open)
Introduction To improve surgical quality and safety, health systems must prioritise equitable care for surgical patients. Racialised patients experience worse postoperative outcomes when compared with non-racialised surgical patients in settler colonial nation-states. Identifying preventable adverse outcomes for equity-deserving patient populations is an important starting point to begin to address these gaps in care. To derive literature-based estimates of the outcome gap for racialised surgical patients, we will systematically review and meta-analyse rates of adverse postoperative events associated with common and/or high-risk operations performed in Canada and the USA.Methods and analysis An electronic search of Medline, Embase, Web of Science, Cochrane Central, CINAHL and Scopus will be conducted to identify studies reviewing complication rates of racialised compared with non-racialised patients from inception to December 2023. We will include publications from the USA and Canada comparing surgical outcomes of racialised and non-racialised patients. The procedures of interest will be the four most common (hip arthroplasty, knee arthroplasty, appendectomy and cholecystectomy), and the five highest risk (oesophagectomy, abdominal aortic aneurysm, aortic valve replacement, coronary artery bypass graft and pancreatectomy) surgical procedures performed in these countries. The outcomes will be mortality, length of stay in hospital, readmission, reoperation, wound dehiscence, surgical site infection, pulmonary embolism, sepsis or septic shock, pneumonia, blood transfusion, stroke, myocardial infarction and bile duct injury. Summary estimates of cumulative incidence, prevalence, incidence rate and occurrence rate of complications using DerSimonian and Laird random effects models will be calculated for the systematic review and meta-analysis. Heterogeneity in these estimates will be examined using subgroup analyses and meta-regression.Ethics and dissemination This study uses secondary data and, therefore, does not require ethics approval. This study will be communicated through presentations at international conferences and published in peer-reviewed literature. The results from this study will inform the development of future surgical equity tools and quality improvement programmes and provide benchmarks on the impact of racism on surgical outcomes.PROSPERO registration number CRD42024491439.